Nurses’ Experiences In Providing Spiritual Care For Patients In Islamic Hospital Banjarmasin - M Fahrin Azhari (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Spiritual need is a basic human need that must be fulfilled. Spirituality is a basic human need that inevitably fulfills, 90% of clients in some areas of America rely on religion as part of the spiritual aspect to gain comfort and strength when they feel seriously ill. This study aims to obtain a picture of the experience of nurses in fulfilling the spiritual needs of patients at Banjarmasin Islamic Hospital. The method used in this research is qualitative method with phenomenology design. The data were collected by involving six participants with in-depth interviews. The participants are the room nurses from the head of the room, the team leader to the nurses who work in the inpatient room of Banjarmasin Islamic Hospital with the age range 32-47 years, and the working period for 5-10 years. The results of the research There are four themes identified in this study: (1) the nurse's efforts to fulfill the spiritual needs, (2) the obstacles of spiritual fulfillment, (3) the nurse's expectation toward the fulfillment of spiritual needs, (4) the support given by the management Hospital. The conclusion of this research is that the nurses' spiritual needs are in the form of efforts to foster the spirit of the patient and help the patient to practice spiritual spirituality in increasing faith in God by collaborating with religious spiritual counselors. Keywords: Nurse Experience, Spiritual Needs, Religious.